A continued struggle for deserving effective services in South African municipalities - Vyas-Doorgapersad, Shikha (Edelweiss Applied Science and Technology, 2025)
The socioeconomic demography of a municipality impacts the delivery of services within its areas of jurisdiction. In the case of South African municipalities, this statement is evidenced by poverty, unemployment, and service delivery protests. This situation is observed from the perspective of community members, who are the end users of unsatisfactory services. From the municipal viewpoint, the lack of financial, human, and infrastructural resources contributes to ineffective service delivery. The fact remains that municipalities are failing to deliver on their mandate of effective and efficient service delivery. The lack of financial resources and economic viability remains challenging, as this inadequacy causes municipalities to incur debts. The lack of human resources is a challenge that demands capacity-building interventions to equip municipal personnel to deliver improved services. This article explores various municipal challenges identified in a qualitative study that conducted literature and document reviews to gather information. The information was analyzed through conceptual and document analysis. The findings confirm that municipalities require transformation. In terms of practical implications, a shift from traditional modes of operation is needed to implement electronic services (e-services), and municipalities must adapt to electronic governance and the Fourth Industrial Revolution (4IR) interventions to improve service delivery. This article concludes by proposing recommendations for improvement based on the literature review.